PEMANFAATAN SEMUT PREDATOR MYOPOPONE CASTANEA (HYMENOPTERA: FORMICIDAE) UNTUK MENGENDALIKAN HAMA KUMBANG TANDUK ORYCTES RHINOCEROS (COLEOPTERA: SCARABAEIDAE) - Widihastuty Widihastuty; Rini Susanti; Wizni Fadhillah (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
The coconut rhinoceros beetle Oryctes rhinoceros is one of the key pests in oil palm plantations. Controls carried out by farmers always use insecticides, which can adversely affect the agroecosystem. Community Service Activities carried out to introduce and provide understanding to partner farmers about alternative controls that are more environmentally friendly by utilizing the natural enemies of predator ants Myopopone castanea. The method used in this service is the extension method. The result is that farmers understand that the ants they usually find in their oil palm plantations are friends for oil palm farmers, so their existence must be maintained so that they can benefit the farmers and the oil palm plantation environment.